2016
DOI: 10.1111/1440-1630.12336
|View full text |Cite
|
Sign up to set email alerts
|

Capturing everyday experiences of typically developing children aged five to seven years: A feasibility study of experience sampling methodology

Abstract: The ESM holds promise for examining the impact of environmental context on everyday experiences of young typically developing children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…Despite these challenges, the feedback that participants reported that they enjoyed participating in the study suggests that modifying ways to enhance future participation are worth pursuing. The average response rate of survey completion (33.8%) was lower than reported in other studies investigating everyday social experience with similar procedure, such as 47.6% in typically developing young children (Mulligan, Schneider, & Wolfe, 2000;Vilaysack et al, 2016), 56.8% in children with ASD (Chen et al, 2015) and around 71% in adults with ASD (Chen et al, 2014;Hintzen et al, 2010). However, it was above the suggested acceptable response rate of 33% (Chen et al, 2014;Hintzen et al, 2010;Myin-Germys et al, 2003).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Despite these challenges, the feedback that participants reported that they enjoyed participating in the study suggests that modifying ways to enhance future participation are worth pursuing. The average response rate of survey completion (33.8%) was lower than reported in other studies investigating everyday social experience with similar procedure, such as 47.6% in typically developing young children (Mulligan, Schneider, & Wolfe, 2000;Vilaysack et al, 2016), 56.8% in children with ASD (Chen et al, 2015) and around 71% in adults with ASD (Chen et al, 2014;Hintzen et al, 2010). However, it was above the suggested acceptable response rate of 33% (Chen et al, 2014;Hintzen et al, 2010;Myin-Germys et al, 2003).…”
Section: Discussioncontrasting
confidence: 56%
“…For example, in the study of four young adults with ASD who commonly present repetitive patterns of behaviours (Chen et al (2014)), participants were able to switch between their current activity and the survey without problems, even though it is not clear what these participants were doing during the day. By contrast, Vilaysack et al (2016) reported that some children could use the device while at school if the mobile device was set to vibrate. Such a strategy may not always be possible for most people with intellectual disability while at work or other vocational activities, for example one of our participants worked in a kitchen where safety issue precluded the use of a mobile device.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This review shows that a smartphone-based EMA design is feasible to use in all types of samples, ranging from adolescents to older participants. Vilaysack et al (2016) showed that it is even feasible to perform smartphone-based EMA research in 5-7 year old children. With the increasing rate of smartphone users around the world and simple design of an application, more people can be reached in a smartphone study that are otherwise not included in research.…”
Section: Samplingmentioning
confidence: 99%
“…The exploratory study by Vilaysack, Cordier, Doma and Chen () is the first to examine the feasibility and appropriateness of using experience sampling methodology (ESM) in children as young as five years of age, using an Android © device as a medium for data collection. The survey software application enabled the researchers to embed images, which could be easily understood by young children, to augment the ESM survey questions; this accommodated variable literacy skills of young children.…”
mentioning
confidence: 99%